Type 1 diabetes and long-term continuous subcunatenous insulin infusion therapy: a 10-year experience from - Petrovski, Goran; Zivkovic, Marija; Shubeska Stratrova, Slavica; Todorovska Jovanovska, Biljana (Mary Ann Liebert, 2017)
Background: Subcutaneous insulin infusion (CSII) therapy is a challenge for both patients and healthcare providers. The long-term CSII use is scarce. The aim of this study is to describe the impact of CSII therapy for 10 years of use at our center. Methods: This single-center retrospective study includes 162 type 1 diabetes patients using CSII for >3 years during October 2004 until October 2014. Data were collected through the electronic medical record system, cross-sectional analysis (telephone, e-mail, or social media), and CSII reports generated by Carelink Therapy Management Software (Medtronic, Northridge, CA). Results: Patients were analyzed in three age groups: 12–18, 19–24, and >25 years. All patients were treated with CSII for >3 years. Total daily dose of insulin was >0.9 U/(kg·day) in age group 12–18 years old, which was significantly higher than other two age groups (P < 0.05). Basal ratio was lower in younger age (<40%) and showed trend of increasing with age and longer diabetes duration (up to 44%). Younger patients used bolus wizard on regular basis (>75%), which was significantly higher than other age groups (P < 0.05). More than 50% of patients achieved glycated hemoglobin (HbA1c) <7.0% and >70% of patients achieved HbA1c <7.5%. HbA1c level significantly changed from baseline in all groups (P < 0.05). Conclusion: Our study shows improved glucose control in long-term CSII users. A reduction of HbA1c levels by −1.1% was maintained during the study period.
Keywords: Continuous subcutaneous insulin infusion; Type 1 diabetes; Long-term therapy